Rhizospheric plant growth-promoting bacteria (PGPR) in corn plants - Soto-Valenzuela, Javier; Andrade-Yucailla, Verónica; Solís-Lucas, Ligia; Vera-Rodríguez, José; Muyudumbay, Allison; Perero-Perero, Anthony (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2026)
PGPR are considered a sustainable alternative to improve crop productivity, for its ability to biostimulate plant growth, induce systemic resistance, increasing tolerance to abiotic stress, among other benefits. The objective of the study was to evaluate the effect of plant growth-promoting rhizosphere bacteria (PGPR) on the germination and development of corn plants. Seven strains obtained from the Biotechnology Research Center (CEB) of the Santa Elena Peninsula State University, Ecuador, were reactivated, corn seeds were inoculated, and planted to evaluate germination and plant development in two stages (laboratory and nursery). The rhizobacteria significantly promoted germination by up to 17 %, emergence, and initial growth of corn, especially the species Stenotrophomonas pavanii and Pantoea dispersa. In addition, P. dispersa (b) species increased stomatal density on both leaf surfaces, which could be associated with better photosynthetic efficiency and water use. In conclusion, S. pavanii and P. dispersa strains promote germination and growth of Azor corn, the phylogenetic analysis indicates close groupings with reference isolates for their efficacy with significant potential such as (PGPR) with documented biotechnological capabilities for the genera Pantoea and Stenotrophomonas.